2021
DOI: 10.2147/imcrj.s322301
|View full text |Cite
|
Sign up to set email alerts
|

Distal Deep Vein Thrombosis in a Patient Cured of Severe COVID-19 Pneumonia at Jimma, Oromia, Ethiopia 2021: A Rare Case Report

Abstract: Background Deep vein thrombosis (DVT) is commonly identified and diagnosed in the emergency department. Factors including sedentary life (immobility), pregnancy in women, cancer, postoperation, admission to ICU, smoking, and obesity are identified risks for thrombosis development. We report a case of a 35-year-old man who presented to the emergency department developing left lower leg swelling and pain, low-grade fever, and headache after he was treated and discharged, cured of severe COVID-19. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In other studies of COVID-19 patients, Hesam-Shariati et al and Debela et al reported patients presenting with typical symptoms of DVT involving leg swelling, redness, calf tenderness, and decreased limb mobility [12,13]. While our patient was clinically asymptomatic, DVT was suspected based on persistently elevated Ddimer levels for several weeks post-recovery and confirmed by Doppler ultrasonography.…”
Section: Discussionsupporting
confidence: 52%
“…In other studies of COVID-19 patients, Hesam-Shariati et al and Debela et al reported patients presenting with typical symptoms of DVT involving leg swelling, redness, calf tenderness, and decreased limb mobility [12,13]. While our patient was clinically asymptomatic, DVT was suspected based on persistently elevated Ddimer levels for several weeks post-recovery and confirmed by Doppler ultrasonography.…”
Section: Discussionsupporting
confidence: 52%
“…Although there are many articles in the literature on supplying and drainage of the foot and ankle, the rate of cadaver dissection studies especially on venous drainage are very few. Beyond all veins of the leg and foot, the most important disorder for the veins is DVT which can cause motor functions deficiency in the lower limb, especially in the elderly patients [4].…”
Section: Discussionmentioning
confidence: 99%